Investigation the Role of Carotenoid Cleavage Dioxygenases in the Synthesis of Apocacrotenoids in Dunaliella Salina: Potential for Stress - Induced Metabolite Production - Hussein, Zainab Nader; Zubaidiyah, Al- (American Journal of Biodiversity, 2025)
Carotenoid cleavage dioxygenases (CCDs) are vital in the production of carotenoids into apocarotenoids- bioactive compounds that are used in stress responses and metabolism. Although they have been well-characterized in higher plants, their role in halotolerant microalgae is not well understood. The present research involves the determination of the effect of CCD1 and CCD4 in the production of apocarotenoid in Dunaliella salina in different abiotic stress situations with the aim of clarifying their regulatory relationship and metabolic impact. The cultures of D. salina were subjected to harsh saline (3.0 M NaCl), bright (600 umol photons m-2 s-1) and oxidative stress (1.0 mM H 2 O 2). The growth rate, morphological changes were captured, and the expression of genes in the form of qRT-PCR were performed on DsCCD1 and DsCCD4. The extraction and quantification of carotenoid-derived apocarotenoids were done using HPLC and validated using LC-MS/MS; stress-responsive cis-elements were analyzed in promoter regions of the CCD genes and correlation analysis done between gene expression and metabolite levels. Exposure to stress had an important negative effect on growth with a percentage reduction of 44.9 in comparison to control being caused by oxidative stress. The expression analysis showed that DsCCD1 (3.45-fold under salinity) and DsCCD4 (2.18-fold under salinity) were strongly upregulated. The level of accumulation of apocarotenoids also significantly increased: b-ionone (0.12 +- 0.02) became 0.38 +- 0.05 ug/mg dry weight and retinal (0.08 +- 0.01) became 0.21 +- 0.03 ug/mg under high salinity. Pearson correlation coefficients between CCD1-b-ionone and CCD4-retinal were 0.92 and 0.88 (p < 0.005). The elements of transcriptional control through stress-receptive pathways were identified as ABRE, DRE, and HSE elements by the promoter analysis. This work validates the role of CCD1 and CCD4 in the apocarotenoid biosynthesis in response to stress in D. salina and their role in adaptive metabolic reprogramming. These results open the prospects of using microalgae as a target of metabolic engineering to produce specific apocarotenoids under eco-friendly conditions.